Khat use and associated factors during pregnancy in eastern Ethiopia: A community-based cross-sectional study - Tadesse Misgana; Dejene Tesfaye; Daniel Alemu; Berhe Gebremichael; Dawit Tamiru; Mandaras Tariku; Adisu Birhanu Weldesenbet; Merga Dheresa (Frontiers Media S.A., 2022)
IntroductionWomen of reproductive age are increasingly using khat. The use of khat is associated with prelabor rupture of membranes, anemia among pregnant women, and other problems related to motherhood and infanthood. Most of the previous studies performed at the facility level revealed that different factors were associated with khat use among pregnant women. Lower educational status, low wealth index, and the age of the mother were the factors significantly associated with maternal khat use. Partner substance use also has a significant association with maternal khat use. However, there is limited information about khat use and its associated factors among pregnant women in the study area.ObjectiveThis study aims at assessing the prevalence of khat use and associated factors among pregnant women in Kersa and Haramaya Health and Demographic Surveillance System Sites, eastern Ethiopia.MethodsA community-based cross-sectional study design was employed among randomly selected 1,015 pregnant women from an open cohort from Kersa and Haramaya Health and Demographic Surveillance System Sites in Ethiopia. Data were collected through face-to-face interviews from January 30 to April 30, 2021, using Open Data Kit (ODK) software and analyzed using SPSS v-26. Descriptive statistics were used to summarize the characteristics of pregnant women. Factors associated with khat use were identified by bivariate and multivariable logistic regression analyses; an adjusted odds ratio (AOR) with a 95% confidence interval (CI) was estimated. Statistical significance was declared at p < 0.05.ResultsThe prevalence of khat use among pregnant women was 15.5% (95% CI, 13.3-17.7). Age of the pregnant women; being in the age group between 25 and 35 years (AOR = 2.27, 95% CI, 1.33-4.89) and 35 years and greater (AOR = 2.33, 95% CI, 1.29-4.20); having a chronic medical illness (AOR = 3.28, 95% CI, 1.27-8.48); and having a history of abortion (AOR = 2.87 95% CI, 1.73-4.76) significantly increased the likelihood of khat use among pregnant women.ConclusionThe current study revealed a relatively high magnitude of khat use in pregnant women as compared with previous studies. The age of the pregnant women, history of medical illness, and history of abortion were significantly associated with khat use during pregnancy.